Values in the post-social world - Marody, Mirosława (Journal of Public Governance, 2017)
In the majority of contemporary sociological studies values are considered to be attributes of persons and are analyzed in terms of their role in motivating individual behaviour. In this text it is assumed that values are a product of collective processes, they emerge through sharing meanings and senses that are worked out in the course of social practices. Therefore, they have a very important function in the society: they legitimize the system, make institutions meaningful, define the direction of action for social actors. Using the concept of a post-social world coined by A. Touraine, in which social actors are replaced with moral ones, the author studies the values around which such actors organize their activity.